2020
DOI: 10.1007/978-3-030-58147-3_52
|View full text |Cite
|
Sign up to set email alerts
|

Motion Guidance Using Translational Force and Torque Feedback by Induced Pulling Illusion

Abstract: It is known that humans experience a kinesthetic illusion similar to a pulling sensation in a particular direction, when subjected to asymmetric vibrations. In our previous study, we developed a device that can apply a translational force and a torque to induce this illusion. The illusory translational force might induce a reaching motion of the upper limb, and the applied torque might induce a flexion-extension motion of the wrist. In the present study, we experimentally verified whether these motions can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…For each cue, these requirements were compared (TABLE I). In our previous study, we demonstrated that an upper limb motion can be induced by applying the illusory pulling cue to the user's finger tips using non-grounded vibrators [32]. Therefore, all requirements in Table I can be achieved using illusory pulling cues.…”
Section: Basic Concept Of a White Cane Techniques Training System Usi...mentioning
confidence: 97%
“…For each cue, these requirements were compared (TABLE I). In our previous study, we demonstrated that an upper limb motion can be induced by applying the illusory pulling cue to the user's finger tips using non-grounded vibrators [32]. Therefore, all requirements in Table I can be achieved using illusory pulling cues.…”
Section: Basic Concept Of a White Cane Techniques Training System Usi...mentioning
confidence: 97%
“…The real challenge is faced in capturing the hidden connotations when such items are translated to, for instance, Arabic. The notion of "translational force" postulates that certain words, by virtue of their flexibility and dynamism, carry a unique communicative ability and are hence, open to translation confusion (Lee et al, 2019;Tanabe et al, 2020). The verbs 'come' and 'go', among a few others, in the English language exemplify this translational force, stemming from the wide range of polysemous meanings associated with them.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism by which the illusion occurs is not entirely clear, previous researchers have discussed the role of mechanoreceptors [8], the influence of skin deformation [10], and cerebral functions [11] in relation to this illusion. Typical applications of the illusory directional sensation were force feedback [12], navigation [13], [14], and motion guidance for upper-limb [15], [16]. We have specifically focused on the utility of motion guidance and have developed a training system utilizing this illusion for white-cane orientation in patients with visual impairment [17].…”
Section: Introductionmentioning
confidence: 99%